2020
DOI: 10.1007/s13300-020-00778-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy and Safety of Rosuvastatin/Ezetimibe Combination Therapy and Rosuvastatin Monotherapy on Lipoprotein in Patients With Type 2 Diabetes: Multicenter Randomized Controlled Study

Abstract: Introduction: Ezetimibe/statin combination therapy has been reported to provide additional cardioprotective effects compared to statin monotherapy. The apolipoprotein B/A1 (apoB/ A1) ratio is an effective predictor of cardiovascular diseases. The aim of this study was to compare the efficacy and safety of rosuvastatin/ezetimibe combination therapy versus rosuvastatin monotherapy using the apoB/A1 ratio in patients with diabetes and hypercholesterolemia. Methods: In this randomized, multicenter, open-label, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…In a study conducted by Lee and others, 47.1% of patients who achieved a reduction in LDLcholesterol !50% during 8 weeks of administration of rosuvastatin 5 mg/day and 76.5% achieved similar reductions when administering rosuvastatin 5 mg þ ezetimibe 10 mg/day. 19 The disparity in these and the present findings may relate to differences in the duration of treatment and characteristics of the groups before treatment; for example, the higher HOMA-IR in the previous study. We also assessed the change in MIG6 concentration during cholesterol-lowering treatment in the entire cohort, and found that this significantly increased.…”
Section: Discussioncontrasting
confidence: 69%
“…In a study conducted by Lee and others, 47.1% of patients who achieved a reduction in LDLcholesterol !50% during 8 weeks of administration of rosuvastatin 5 mg/day and 76.5% achieved similar reductions when administering rosuvastatin 5 mg þ ezetimibe 10 mg/day. 19 The disparity in these and the present findings may relate to differences in the duration of treatment and characteristics of the groups before treatment; for example, the higher HOMA-IR in the previous study. We also assessed the change in MIG6 concentration during cholesterol-lowering treatment in the entire cohort, and found that this significantly increased.…”
Section: Discussioncontrasting
confidence: 69%
“…Combination treatment with ezetimibe and a statin, as a result of a synergistic effect, results in greater LDL-C concentration decrease than monotherapy with either agent [ 168 ]. Ezetimibe added to a statin reduces LDL-C concentration by another 15–20%; therefore, a combination of high-intensity statin treatment (i.e., atorvastatin or rosuvastatin at their highest doses) with ezetimibe can reduce LDL-C concentration by up to 65–70% [ 8 , 9 ].…”
Section: Principles Of Pharmacological Treatment Of Lipid Disordersmentioning
confidence: 99%
“…Ezetimibe added to a statin reduces LDL-C concentration by another 15–20%; therefore, a combination of high-intensity statin treatment (i.e., atorvastatin or rosuvastatin at their highest doses) with ezetimibe can reduce LDL-C concentration by up to 65–70% [ 8 , 9 ]. This combination is more effective (by more than 15 mg/dl) in terms of LDL-C reduction and 2.45 times more effective in achieving the treatment goal as compared to doubling the statin dose [ 155 , 168 ]. Unfortunately, the combination of a statin with ezetimibe is still very rarely used not only in Poland and in Europe, but also worldwide, even though for 4 years ezetimibe has been a generic and very cheap product.…”
Section: Principles Of Pharmacological Treatment Of Lipid Disordersmentioning
confidence: 99%
“…Therefore, the ApoB/ApoA-Ι ratio is the simplest form of re ecting the balance of cholesterol transport in the body. The larger the ratio of ApoB/ApoA-Ι, the more cholesterol is present in the blood circulation, and the easier it is to deposit in the blood vessel wall, which will promote the occurrence of atherosclerosis and cardiovascular events [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%